THE CHARACTER DEVELOPMENT OF INDEPENDENCE ELEMENTARY SCHOOL STUDENTS THROUGH THE MODEL T-CAR (THINK-CHOOSE-ACT-REFLECT) - Nurhikmah, Irma (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2017)
This study aims to improve the character of Independence Elementary School Students using learning models T-CAR (Think, Choose, Action, Reflect). This study was conducted in SD Amaliah Ciawi. This model shows the stages of how to build the character of students independence that constituted with the application on the pattern of thought (think). The application of this mindset influence the decision of the election (choose). So when the child has decided on his choice, he would do (action) what he chose. That would form a conclusion that something that he did have his own impact both positive and negative (reflect). This research used experimental research trials conducted by 2 stages of testing and evaluation. The results of this trial demonstrate a significant difference through T-test analysis techniques with the results of T count is greater than the T-table by 4,85>2,06. From these results it can be concluded that the use of the model T-CAR can improve the character of elementary school students independence. Therefore, the model T-CAR can be used as one of the strategies in teaching in schools to develop students' independence.